Non-contrast-enhanced magnetic resonance venography using magnetization-prepared rapid gradient-echo (MPRAGE) in the preoperative evaluation of living liver donor candidates: Comparison with conventional computed tomography venography. Issue 90 (May 2017) - Yamashita, Rikiya; Isoda, Hiroyoshi; Arizono, Shigeki; Ono, Ayako; Onishi, Natsuko; Furuta, Akihiro; Togashi, Kaori
Highlights: MPRAGE-MRV and CTV showed similar performance in evaluation of RL-LDLT without MHV. MPRAGE-MRV tended to show more venous tributaries than conventional CTV. MPRAGE-MRV could replace CTV for preoperative evaluation of living liver donors. Abstract: Objective: To compare the diagnostic performance of non-contrast-enhanced magnetic resonance venography using magnetization-prepared rapid gradient-echo (MPRAGE-MRV) and conventional computed tomography venography (CTV) in preoperative evaluation of venous tributaries for living donor liver transplantation. Materials and methods: Institutional review board approval and written informed consent were obtained for this prospective study of 73 donor candidates. Of these, 23 underwent right-sided graft hepatectomy without middle hepatic vein. One or more tributaries, other than the right hepatic vein, were reconstructed for 20 of the 23 grafts. For these 20 grafts, the number and location of the tributaries requiring reconstruction were evaluated based on venography, and diagnostic performance was analyzed using surgical records as a reference standard. For each candidate, the number of small tributaries directly joining the inferior vena cava was counted in each venographic image; a paired-sample t -test was used to assess differences. The severity of respiratory artifacts in MPRAGE-MRV was qualitatively evaluated, and compared using Wilcoxon's rank-sum test. Results: All reconstructed venous tributaries were prospectively identified using both methods. MPRAGE-MRV tended to provide a greater number of small tributaries than conventional CTV (mean: 2; 95% CI: [1.66, 2.34], and 1.74; [1.44, 2.04], respectively), although the difference was not significant ( P  = 0.10); MPRAGE-MRV was superior or equal to CTV in 52 subjects (71.2%), and inferior in 21 subjects (28.8%). Respiratory artifacts were significantly less severe in the former subjects ( P  < 0.0001). Conclusions: MPRAGE-MRV has the potential to replace conventional CTV in the preoperative evaluation of living liver donor candidates.